2013
DOI: 10.1177/0306624x12472956
|View full text |Cite
|
Sign up to set email alerts
|

A Consumer Satisfaction Survey of Civilly Committed Sex Offenders in Illinois

Abstract: The purpose of this study was to obtain feedback from civilly committed sex offenders (N = 113) about the components of treatment that they believed to be most important and helpful in preventing reoffense. Participants were also asked to rate their satisfaction with the treatment process and therapists. Victim empathy and accountability were rated as the most important elements of treatment, along with skills for preventing relapse and methods for controlling sexual arousal. There was a fairly robust correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…As a function of sex offenders having a greater amount of interaction with clinical specialists and the dynamics of treatment, it was probable that sex offenders were more likely to discuss their personal difficulties with clinical specialists than community corrections professionals, which may, in turn, have influenced the perceptions of these toward current sex offender management policies. The literature has shown that sex offenders generally have positive attitudes about their therapists and are comfortable sharing personal information with them (Levenson, Prescott, & D'Amora, 2009;Levenson, Macgowan, Morin, & Cotter, 2009;Levenson, Prescott, & Jumper, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As a function of sex offenders having a greater amount of interaction with clinical specialists and the dynamics of treatment, it was probable that sex offenders were more likely to discuss their personal difficulties with clinical specialists than community corrections professionals, which may, in turn, have influenced the perceptions of these toward current sex offender management policies. The literature has shown that sex offenders generally have positive attitudes about their therapists and are comfortable sharing personal information with them (Levenson, Prescott, & D'Amora, 2009;Levenson, Macgowan, Morin, & Cotter, 2009;Levenson, Prescott, & Jumper, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical specialists in the present study were significantly more likely to both have contact with sex offenders and provide treatment to sex offenders than the community corrections professionals. The literature has shown that sex offenders generally have positive attitudes about their therapists and are comfortable sharing personal information with them (Levenson, Macgowan, Morin, & Cotter, 2009; Levenson, Prescott, & D’Amora, 2010; Levenson, Prescott, & Jumper, 2014). It is probable that sex offenders are more likely to discuss their personal difficulties with clinical specialists than community corrections professionals due to the dynamics of the treatment process and the greater amount of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a relevância deste trabalho é verificada ao encontrar dados que corroboram evidências retratadas pela literatura da área. No entanto, fazem-se necessários mais estudos acerca do fenômeno estudado, com grupos maiores e com outros métodos projetivos, como sugerido por outros investigadores da área (Achá, Rigonatti, Saffi, Barros, & Serafim, 2011;Beech, Bartels, & Dixon, 2013;Davis & Archer, 2010;Levenson, Prescott, & Jumper, 2014;Willians & Finkelhor, 1990).…”
Section: Discussionunclassified